Laboratory simulation of airflow and atmospheric transport-dispersion over Elk Mountain, Wyoming: technical report - Kitabayshi, K., author; Orgill, Montie M., author; Cermak, J. E. (Jack E.), author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1971)
A stably stratified airflow over an isolated mountain was simulated in a wind tunnel and transport-dispersion properties were investigated. Geometric, dynamic and thermal similarity were considered for stably stratified airflows. The wind tunnel airflow was compared with the field results and also with computer results by Marwitz et al. The agreement of these three systems was fairly good and shallow-water equation system was shown to be a possible mathematical model for this kind of airflow. Vertical and horizontal dispersion were investigated for a source at ground level on the upwind side of the mountain. The lateral and vertical dispersions were qualitatively simulated in wind tunnel. The vertical dispersion was found to be strongly controlled by the existing inversion. From observations of smoke transport, the blocking effect of the mountain was found to be strengthened by stable density stratification.
CER70-71KK-MMO-JEC65.
July 1971.
Prepared under Atmospheric Water Resources Research Division of the Bureau of Reclamation contract nos. 14-06-D-6455 and 14-06-D-6842.
Keywords: Wind tunnel models